BUMDES as a Hybrid Institution: Dynamics of Power Relations and Social Legitimacy in Realized Village Independences - An' Amta, Dimas Asto Aji; Hidayah, Sri; Al Syahrin, M. Najeri; Fadly, Faldy; Bakhsar, Intan Septiana; Amalia, Dinda Fitri (Publikasi Berkala Pendidikan Ilmu Sosial, 2026)
Village-Owned Enterprises (BUMDes) are positioned as strategic instruments for fostering rural self-reliance through the collective management of local resources. In practice, BUMDes function not only as economic entities but also as socio-political arenas characterized by complex dynamics of power relations, conflicts of interest, and negotiations among village actors. This study aims to analyze the social dynamics in the management of BUMDes by comparing two village cases in Karang Intan Subdistrict, namely Mandi Kapau Timur Village and Sungai Landas Village. This research employs a qualitative approach using Participatory Action Research (PAR), involving participatory observation and in-depth interviews. The analysis is conducted through the perspectives of hybrid institutions and the bundle of rights framework. The findings reveal two distinct developmental trajectories of BUMDes: a consolidative pathway and a fragmentative pathway. Mandi Kapau Timur Village demonstrates institutional consolidation through clear business differentiation, equitable benefit distribution, and strong social legitimacy, which collectively drives socio-economic transformation. In contrast, Sungai Landas Village exhibits business fragmentation that directly competes with local livelihoods, leading to conflicts of interest and weakening social legitimacy. These findings highlight that BUMDes success is shaped not only by capital or business type, but by the ability to balance economic and social dimensions, align collective and individual interests, and manage power relations inclusively. Accordingly, recommendations for BUMDes development should be accompanied by strengthening socio-political governance, and villages must ensure business differentiation that does not directly compete with local economic activities.